2012
DOI: 10.1038/ejcn.2012.95
|View full text |Cite
|
Sign up to set email alerts
|

Mid-upper-arm-circumference and mid-upper-arm circumference z-score: the best predictor of mortality?

Abstract: BACKGROUND/OBJECTIVE: Mid-upper-arm circumference (MUAC) is a simple method of assessing nutritional status in children above 6 months of age. In 2007 World Health Organization (WHO) introduced a MUAC z-score for children above 3 months of age. We evaluated whether MUAC or MUAC z-score had the best ability to identify children with high short-term mortality risk in Guinea-Bissau. SUBJECTS/METHODS: The Bandim Health Project visits children 3-monthly until 3 years of age. MUAC is measured and deaths are register… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
42
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 4 publications
3
42
0
Order By: Relevance
“…MUAC is a valid measure of nutritional status and a good predictor of mortality [16, 19]. The finding that early MV had a positive effect on MUAC among girls at 24 months corresponds with previous studies from the same trial concluding that the effects of early MV were strongest among girls.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…MUAC is a valid measure of nutritional status and a good predictor of mortality [16, 19]. The finding that early MV had a positive effect on MUAC among girls at 24 months corresponds with previous studies from the same trial concluding that the effects of early MV were strongest among girls.…”
Section: Discussionsupporting
confidence: 75%
“…MUAC was not converted to Z-score as the recommendation for MUAC cutoffs is not valid for children under 6 months of age [14, 15]. Furthermore, we have found that MUAC is as good a predictor of mortality as MUAC z-score [16]. …”
Section: Methodsmentioning
confidence: 99%
“…Others also reported similar findings [15,16]. As the growth reference values and MUAC are lower in girls [30,35], a single cut-off to define acute malnutrition may result in over diagnosis of the condition in girls compared with indicators that are standardized for age and sex [15,36]. While our results show the prevalence of wasting in boys to be higher than girls when WHZ was used, there was no sex-difference when MUAC was used.…”
Section: Discussionmentioning
confidence: 70%
“…[17][18][19][20] Within this age group, adjusting MUAC by calculating the Z score or adjusting for height does not improve MUAC's predictive value. 21 MUAC can be measured easily, quickly and affordably. Values below the cut-offs of 125 mm and 115 mm are used to define moderate and severe acute malnutrition, respectively.…”
Section: Introductionmentioning
confidence: 99%